2019
DOI: 10.1111/inm.12657
|View full text |Cite
|
Sign up to set email alerts
|

‘There need to be a balance’: Mental health nurses’ perspectives on medication education in university and clinical practice

Abstract: Working with medication is an important role of the mental health nurse. However, little research has focused on staff nurses’ perspectives on where the responsibility lies for preparing student nurses for safe, competent medication management. This study investigated mental health nurses’ perspectives on medication education. An interpretive descriptive approach was used. Two focus groups were conducted, and data were analysed using inductive content analysis. It was found that participants embraced a medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…Particularly, MHNs working in the inpatient setting position themselves closely with the biomedical model, suggesting that medication is still very much the focus and that there is a culture of over‐reliance on medication prescribed by psychiatrists. This finding concurs with a recent study that showed that MHNs still have a preference for a medical approach to care delivery (Goodwin et al., 2020). Thus, this impacts negatively on how MHNs’ offer PSI.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, MHNs working in the inpatient setting position themselves closely with the biomedical model, suggesting that medication is still very much the focus and that there is a culture of over‐reliance on medication prescribed by psychiatrists. This finding concurs with a recent study that showed that MHNs still have a preference for a medical approach to care delivery (Goodwin et al., 2020). Thus, this impacts negatively on how MHNs’ offer PSI.…”
Section: Discussionsupporting
confidence: 92%
“…Member checking was not used, as responses by participants can be considered to constitute new data. Instead, throughout each interview, clarification probes were used to ensure that a comprehensive summary of perspectives was obtained (Goodwin et al, 2020). A traditional pen-and-paper approach was employed, i.e., data analysis software was not used.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the workshop, using a variety of skilled tutors and incorporating a multitude of interactive teaching strategies, such as simulation, provided a suitable pedagogical approach to address the theorypractice gap, something which presents an ongoing challenge for nurse education (Goodwin et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The design of the workshop, using a variety of skilled tutors and incorporating a multitude of interactive teaching strategies, such as simulation, provided a suitable pedagogical approach to address the theory–practice gap, something which presents an ongoing challenge for nurse education (Goodwin et al. 2019b). Here, the use of clinically based nurses using clinical equipment to deliver content on IM medications, an interactive/participatory approach, student presentations, and testing knowledge through a final informal exam were all considered by the students to be favourable approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation